(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the concept of sentence typology and clause structure within the framework of Cognitive Grammar (CG). It delves into how CG views language as a reflection of human cognition, emphasizing the interconnection between sentence forms and mental processes. The article categorizes clause types (declarative, interrogative, imperative, and exclamatory) and discusses how each reflects specific cognitive functions, such as asserting information, inquiring, giving commands, and expressing emotions. Furthermore, it highlights the role of key elements such as the subject, verb, and object in shaping the mental representation of events and actions. By emphasizing constructional schemas and the cognitive relationships between clause elements, the article demonstrates how sentence structure in CG is grounded in our conceptual understanding of the world. This approach provides a deeper understanding of how language reflects thought, moving beyond formal syntactic rules to focus on the cognitive processes that shape linguistic expression.